Effects of virtual reality natural experiences on factory workers’ psychological and physiological stress - Ho, Mu-Hsing; Wu, Meng-Shin; Yen, Hsin-Yen (Frontiers in Psychology, 2023)
This study aimed to explore the effects of virtual reality natural experiences on furniture factory employees’ psychological and physiological stress. A single-blinded, non-randomised quasi-experimental study was conducted between July and December 2021. Factory workers were recruited from two factories, and all participants at a given factory were assigned to either an experimental group or a comparison group. The intervention was conducted in a clean conference room once a week for 12 weeks during the worker's break time. The experimental group received virtual reality natural experiences consisting of 30-minute nature-based 360° videos which were played in a headset. The generalised estimating equations were performed for the statistical analyses. In total, 35 participants completed the intervention. As to psychological stress, the experimental group showed improvements in distress, depression, and anxiety, and a positive affect after the intervention compared to the comparison group. As to physiological stress, the experimental group showed improvements in indicators of heart rate variability compared to the comparison group, including standard deviations of all normal-to-normal intervals, low-frequency power, and high-frequency power. Virtual reality is an innovative platform to bring the natural environment into an indoor environment to create similar health effects.